Magnetization study in solid state formation of lithium-titanium ferrites synthesized by electron beam heating; Materials Chemistry and Physics; Vol. 176 - Surzhikov A. P. Anatoly Petrovich; Lysenko E. N. Elena Nikolaevna; Vlasov V. A. Vitaliy Anatolievich; Malyshev A. V. Andrei Vladimirovich; Vasendina E. A. Elena Aleksandrovna (2016, 2016)
Title screen